What role does agriculture play in irrigation water footprint consumption? A perspective based on sectoral linkage and structural path - Xiaoling Li; Yu Song (Journal of Hydrology: Regional Studies)
Study region: China Study focus: This study employs a novel three-module analytical framework to appraise the linkage effects and structural paths associated with the irrigation water footprint in the agricultural sector from 2002 to 2020. New hydrological insights for the regions: The results showed that a) The agricultural sector exhibits a significant reliance on its own internal water resources, while simultaneously representing a critical source of water resources for other sectors, thus positioning agriculture as a net water resource provider. b) Different from the overall irrigation water footprint, which is upward and then downward, the irrigation water footprint in agriculture is characterized by a downward and then oscillating upward. In addition, the net input irrigation water footprint turned from negative to positive highlighting the significant role of imported water in reducing domestic water scarcity. c) An in-depth analysis of agriculture indicates that direct consumption constitutes the largest component of the irrigation water footprint, with outflow significantly exceeding inflow. From a production standpoint, agriculture and industry represent the primary intermediate consumers of the irrigation water footprint. From a consumption perspective, while the structural paths of the irrigation water footprint vary across different consumers, agriculture consistently functions as the initial sector in irrigation water footprint transmission. These findings provide valuable insights for developing nations to develop effective water management strategies in their respective agricultural sectors.